23-gauge versus 20-gauge system for pars plana vitrectomy: a prospective randomised clinical trial. Issue 11 (14th August 2008) - Wimpissinger, B; Kellner, L; Brannath, W; Krepler, K; Stolba, U; Mihalics, C; Binder, S
Abstract : Aim: To compare the sutureless 23-gauge system with a standard 20-gauge system in pars plana vitrectomy. Methods: 60 patients in two randomised groups were included in this prospective clinical trial. Pars plana vitrectomy with either 23- or 20-gauge instruments was performed. The main outcome measures were postoperative conjunctival injection and pain. Secondary outcome parameters were time of surgery, intraocular pressure, visual acuity and complications. Results: Conjunctival injection (p = 0.0003) and postoperative pain (p = 0.01) were significantly reduced following 23-gauge vitrectomy compared with the 20-gauge procedure. Opening (p = 0.006) and closure times (p<0.00001) were significantly shorter, and vitrectomy time (p = 0.001) significantly longer in the 23-gauge system compared with 20-gauge vitrectomy. However, retinal manipulation and overall surgery times did not differ significantly between both groups. The same applies for eye pressure, distance and reading acuity. Regarding complications, two choroidal haemorrhages and one flat serous choroidal detachment occurred in the 23-gauge group. Conclusion: The 23-gauge system for pars plana vitrectomy offers significantly higher patient comfort during the early postoperative period. Time of surgery is almost equal—a shorter time for wound closure is neutralised by a longer vitrectomy time in the 23-gauge group.